Evaluation and Design of High Frequency Transformers for On Board Charging Applications - Elgström, Tobias; Nordgren, Linus (My University, 2016)
The demand and production of hybrid and full electric vehicles is steadily increasing. This accelerates the development of infrastructure and related systems, such as chargers. When connecting the charging port directly to the grid, chargers integrated into the vehicles converts the AC mains to correct battery voltage and regulates the power. In order to achieve the required galvanic isolation of the battery from the grid, high frequency transformers are normally used. However, designing a power transformer is not trivial since its properties are highly complex to determine. This thesis includes an investigation of the main sources of transformer winding and core losses at high frequency operation. The origin of the losses are presented in a theoretical perspective and quantified for a real case by simulations and measurements. Additionally, two identical 5.5 kW transformers for use in a 11 kW isolated DC-DC stage are designed using a loss calculation model and an optimization algorithm, both developed in this work. The transformers reach an efficiency of above 99.63% under normal operating conditions and the losses are limited to 20.8W in each transformer throughout the full operating range. Moreover, the power density for the designed transformer is 46 kWdm−3 and the total packaging volume is 0.119dm3. It is further studied how the loss characteristics depend on a multiple of parameters and operating points. Quantification of the losses clearly motivates that the harmonic content of the non-sinusoidal waveforms is non-neglectable. The reason is that, in many cases, the majority of the winding losses are caused by harmonics. It is also shown how a well constructed winding alignment and litz wire configuration significantly can reduce losses.
Keywords: Elkraftteknik; Electric power engineering